Elites and Bank-Based Finance: A political economy model on the emergence of financial systems - Florian Buck; Nikolaus Hildebrand (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Why do some economic systems depend on bank financing while others rely on capital markets and bond financing? We propose a political economy model in which elites favor a bank-based system, which increases their rents due to reduced competition. If suffrage is restricted to the elite, this will result in poor corporate control rights and more reliance on banks that offer substitute mechanisms of corporate governance. The lack of legal rights in history triggers path dependencies and explains the dominance of banks until this day. We test the model's predictions by tracking the emergence and evolution of the bank-based financial system in Germany since the 19th century.
Keywords: D72; O16; P16; 330